(untitled) (Research, Society and Development, 2022)
Introduction: There is a discussion of whether HIV/AIDS or antiretroviral treatment is responsible for generalized clinical manifestations involving the auditory system and/or the vestibular system. Objective: To conduct an integrative review on the occurrence of otoneurological signs and symptoms in people living with HIV/AIDS. Method: Utilizing the PICOS criterion to answer the following question: Are HIV/AIDS responsible for generalized clinical manifestations involving the vestibular system? Data collection from the databases: Embase/Elsevier; Lilacs; PubMed; Scopus and Web Of Science, from 2010 to 2021. The following were included: complete articles published Portuguese, English and Spanish, case-control study, cohort study, pilot study, with longitudinal and cross-sectional design, which report otoneurological alterations in people living with HIV/AIDS who underwent vertigo and/or dizziness tests. The key words were based on Decs - Descriptors in Health Sciences - and Mesh Terms in English. The following studies were excluded: abstracts, congress annals, case reports, studies that have a population under the age of 10 years and over 50 years, articles on HIV associated with other basic pathologies, Review articles. Results: The research resulted in 735 studies identified in the databases and after the application of inclusion criteria, 14 articles remained for descriptive analysis. Conclusion: After the conclusion of this literature review, it was possible to observe that there is no consensus in the literature on the effects of the use of antiretroviral therapy on the vestibular system of people living with HIV (PVHIV) or with immunodeficiency syndrome (AIDS).